THE USE OF TELEMEDICINE IN MANAGING ACUTE AND CHRONIC RHEUMATOLOGICAL CONDITIONS IN CHILDREN - Osama Mohammed Alnasser; Hebah Hussein Alameer; Mohammed Mahmmoud Alkhairi; Elyas Mahmoud Alsaati; Amar Abdullateef Softah; Mohammed Abdullah Niyazi; Ahmed Marzouq Alamri; Nidal Abdullah Al Mutaileq; Basel Falah Alanazi; Abdulaziz Ahmed Alkaaboor; Nouf Hayyaf Alamri (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Telemedicine has rapidly emerged as a vital tool in pediatric rheumatology, offering new avenues for diagnosing, monitoring, and managing acute and chronic rheumatological conditions in children. This review examines the integration of telemedicine into pediatric rheumatology, highlighting both the benefits and the challenges associated with its use. Among the key advantages are improved access to specialized care, the ability to conduct continuous monitoring of patients’ conditions, and the reduction in the need for frequent hospital visits. These factors are crucial in managing diseases such as juvenile idiopathic arthritis and lupus, where early intervention and regular monitoring can significantly alter disease progression and improve quality of life. However, the adoption of telemedicine is not without challenges. Issues such as the digital divide, data privacy concerns, and the lack of familiarity with telehealth platforms among patients and providers are significant hurdles. These barriers can hinder the effective implementation of telemedicine, particularly in under-resourced areas. Furthermore, while telemedicine offers remarkable opportunities for remote diagnosis and patient education, it cannot completely replace in-person visits, especially for more complex assessments and treatments that require physical interaction. Future direct in telemedicine in pediatric rheumatology include leveraging artificial intelligence to enhance diagnostic accuracy and treatment personalization, improving the interoperability of health systems to facilitate better data exchange, and expanding the use of wearable devices for more effective patient monitoring. Ensuring equitable access to these technologies and addressing the socioeconomic and technological disparities that exist in healthcare will be essential for maximizing the benefits of telemedicine. This review underscores the need for ongoing research and policy support to overcome these challenges and fully harness the potential of telemedicine in pediatric rheumatological care.